Findings from aetiological investigation of Auditory Neuropathy Spectrum Disorder in children referred to cochlear implant programs. (January 2019) - Rajput, K.; Saeed, M.; Ahmed, J.; Chung, M.; Munro, C.; Patel, S.; Leal, C.; Jiang, D.; Nash, R.
Abstract: Objectives: Auditory neuropathy spectrum disorder (ANSD) is an audiological diagnosis characterised by hearing dysfunction in the presence of intact outer hair cell function in the cochlea. ANSD is thought to account for 7–10% of all childhood permanent hearing impairment, and can result from a range of pathological processes. This paper describes the rationale, methods and findings from the aetiological investigation of ANSD. Methods: Retrospective audit of four cochlear implant programmes. Results: 97 patients were identified. 79% of patients were identified before the age of one. Prematurity and jaundice were the most frequently identified aetiological factors. 33 patients had cochlear nerve deficiency on imaging. Genetic diagnoses identified included otoferlin, SX010 gene, connexin 26 and A1FM1 gene mutations. ANSD was seen in conjunction with syndromes including Kallman syndrome, CHARGE syndrome, X-linked deafness, SOTOS syndrome, Brown Vieletto Van Laere syndrome, and CAPOS syndrome. Discussion: We present a two-level system of aetiological investigation that is clinically practical. Patients with ANSD sufficiently severe to consider cochlear implantation are generally identified at an early age. Aetiological investigation is important to guide prognosis and identify comorbidity. Conclusion: Prematurity and jaundice are the most commonly identified aetiological factors in ANSD. Imaging findings identify crucial factors in a significant minority. An important minority may have genetic and syndromic diagnoses that require further management.